MAKNA SIMBOLIK DAN PENDIDIKAN KARAKTER DALAM TRADISI KEDUK BEJI TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMP - Cahya, Clarissa Nindytya; Wardani, Nugraheni Eko; Saddhono, Kundharu (Universitas Negeri Makassar, 2024)
This research was conducted with the aim of describing the background, symbolic meaning, character education value of the relevance of teaching material ceremony in junior high school Keduk Beji tradition ceremony in Tawun Village. This type of research was conducted using qualitative descriptive method. This research data is in the form of observation, interviews with informants. The data collection technique used is by making observations or observations and conducting interviews. The result of the research is the Keduk Beji ceremony is motivated by the sacrifice of an ancestor named Raden Ludrojoyo who is believed to meditate around Sendang Tawun which eventually became a spring. Each stage of the procession and offerings of the Keduk Beji traditional ceremony used has a symbolic meaning contained, namely as a form of respect for ancestors and gratitude to God by using offerings as offerings to ancestral spirits believed by the surrounding community. The Keduk Beji traditional ceremony contains character education values reflected in the Pancasila profile, such as faith, fear of God, and noble character, mutual cooperation, and global diversity. And the Keduk Beji traditional ceremony has relevance in Indonesian language learning as teaching material for descriptive text by giving assignments in the form of describing the Keduk Beji traditional ceremony procession.